CESAREAN SCAR ECTOPIC PREGNANCY: SURGICAL TREATMENT - Dimitrov, Vanja; Stefanović, Milan; Cvetanović, Vladimir; Nedin Ranković, Gorana; Pop-Trajković, Sonja; Trenkić, Milan (Acta medicae Medianae, 2025)
Cesarean scar ectopic pregnancy is one of the rarest forms of ectopic pregnancy. It occurs in approximately 1 out of 2000 pregnancies. There are many challenges in its diagnosis and management which if not recognised can endanger the patient and provide poor outcomes, with a high rate of maternal morbidity or mortality. In cesarean scar ectopic pregnancies an embryo attaches to the scar tissue from the previous cesarean section and grows in the uterine wall that is not strong, so it may cause life-threatening hemorrhage, leading to a hysterectomy and potential devastating consequences. This is a case report of a 35-year-old pregnant woman, with cesarean scar ectopic pregnancy, who has one cesarean section in her medical history and was treated by ultrasound-guided suction curettage.
Keywords: ectopic pregnancy, cesarean scar, suction curettage